The Raise of Blood Pressure as One of Metabolic Syndrome Parameter in Post Surgical Menopausal Women - Imantika, Efriyan (Fakultas Kedokteran, 2019)
Background Natural menopause is the permanent cessation of menstrual period that is not caused by any type of surgical procedure or medical treatment, while post surgical menopause means surgical removal of both ovaries before the natural age of menopause.1 Its estimated number of menopausal women in Indonesia reached 30.3 million in 2020 except post surgical menopause women. Reduction of estrogen production in oophorectomized women causes early menopause problems such as physical and physiological aspects. Physical aspect causes many reproductive disorders such as vasomotor disturbances , osteoporosis and metabolic disease that affect to the activities of women experiencing menopause. Metabolic syndrome (MS) is accompanying many factors such as hypertension, insulin resistance, obesity and lipid abnormalities and all these factors cause cardiovascular disease and diabetes (10). The prevalence of metabolic syndrome in post menopausal women can change by the region or population but ovarian function is not well known. In this study we investigated blood pressure as one component of metabolic syndrome in post surgical menopause in our population based on indication of procedure. Method A cross sectional study using medical records of the post surgical menopause patient in Sardjito hospital Yogyakarta from January 2011- December 2016. It divided in to two groups based on the indication of surgical procedure. The first group was 31 women with history of bisalphingoooforectomy on indication ovarian cancer and second sub group was 31 women with history of bisalphingoooforectomy on indication endometriosis. Objective To analyse the raise of blood pressure as one of Metabolic Syndrome parameter in post surgical menopausal women. Result There was significant difference of systolic blood pressure between post surgical menopausal women statistically. The systolic blood pressure in malignancy group raised higher than benign group (141.9 ± 11.67 vs 129.67 ± 7.5; p=0.005). Diastolic blood pressure was not significant difference between post surgical menopause women based on indication of surgical procedure (74.5 ± 7.67 vs 72.9 ± 5.9; p=0.07) Conclusion The raise of systolic blood pressure in post surgical menopausal women due to ovarian malignancy was higher than benign then increased the risk of metabolic syndrome.Keyword: Blood pressure, metabolic syndrome, post surgical menopause